2020
DOI: 10.3390/healthcare8040383
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment Response in Chronic Lyme Disease: Why Do Some Patients Improve While Others Do Not?

Abstract: There is considerable uncertainty regarding treatment of Lyme disease patients who do not respond fully to initial short-term antibiotic therapy. Choosing the best treatment approach and duration remains challenging because treatment response among these patients varies: some patients improve with treatment while others do not. A previous study examined treatment response variation in a sample of over 3500 patients enrolled in the MyLymeData patient registry developed by LymeDisease.org (San Ramon, CA, USA). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…They reported that more than 70% of patients referred with “LD” to an academic infectious disease clinic were considered misdiagnosed and >80% of those patients were considered to have received unnecessary antimicrobial therapy. In contrast, another recent study, 27 using data from a patient-derived database, 28 showed that some patients experienced significant benefits from a combination of antibiotic and alternative therapies, and focused medical management.…”
Section: Introductionmentioning
confidence: 95%
“…They reported that more than 70% of patients referred with “LD” to an academic infectious disease clinic were considered misdiagnosed and >80% of those patients were considered to have received unnecessary antimicrobial therapy. In contrast, another recent study, 27 using data from a patient-derived database, 28 showed that some patients experienced significant benefits from a combination of antibiotic and alternative therapies, and focused medical management.…”
Section: Introductionmentioning
confidence: 95%
“…A tissue bank was recently launched for post-mortem and surgical samples. Tissue donors have the option to link their MyLymeData registry profile to their tissue sample (339,340).…”
Section: Lyme Disease Biobankmentioning
confidence: 99%
“…Our analysis suggests that antibiotic related questions may be the most important in predicting a patient's treatment response for those with persistent Lyme disease. This topic is explored in greater detail in a companion study analyzing the role of specific features identified in the top 30 in connection with treatment response [22].…”
Section: Antibioticsmentioning
confidence: 99%
“…In a companion study performed in parallel to this work [22], the authors use more traditional statistical methods and investigative analysis on the MyLymeData dataset. The results of our classification and regression models agree with many of its findings.…”
Section: Comparison With Companion Studymentioning
confidence: 99%